2020
DOI: 10.1007/s11144-020-01824-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on binary copper-based catalysts used in the ethanol steam reforming process

Abstract: The use of copper-based binary catalysts, Cu/Zr oxides and Cu/Al oxides, has been examined to produce hydrogen from ethanol in the ethanol steam reforming process. The examined catalysts were compared with non-noble bicomponent catalysts consisting of oxides of nickel and cobalt: Ni/Zr Co/Zr, Ni/Al and Co/Al, prepared and tested in the identical way. Catalytic tests were carried out in the fixed-bed reactor in the temperature range 433-873 K for initial molar ratio of ethanol to water equal to 1:3. Ethanol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…2c illustrates the advanced ESR hydrogen production performance of the reported non-noble metal catalysts as far as we know. It confirmed that the ESR hydrogen generation rate of Ni SA/CeO 2 was ∼3 times higher than the best reported ESR performances, e.g., Ni-Cu/BEA@Co/MFI (774 mmol g −1 h −1 ), 32 20Ni/ATP (537 mmol g −1 h −1 ), 33 Ni/ ATP-C600 (486 mmol g −1 h −1 ), 34 17Co/MnO x (213 mmol g −1 h −1 ), 35 10Co-7.1Ce/SEP (157 mmol g −1 h −1 ), 36 10Co/SEP (46 mmol g −1 h −1 ), 36 NiO/ZrO 2 (34 mmol g −1 h −1 ), 37 and Ni/ Al 2 O 3 (32 mmol g −1 h −1 ). 37 Except for the high ESR activity, the ESR hydrogen generation rate of Ni SA/CeO 2 fluctuated from 1650 to 1702 mmol g −1 h −1 , in a 24 h successive test at 500 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2c illustrates the advanced ESR hydrogen production performance of the reported non-noble metal catalysts as far as we know. It confirmed that the ESR hydrogen generation rate of Ni SA/CeO 2 was ∼3 times higher than the best reported ESR performances, e.g., Ni-Cu/BEA@Co/MFI (774 mmol g −1 h −1 ), 32 20Ni/ATP (537 mmol g −1 h −1 ), 33 Ni/ ATP-C600 (486 mmol g −1 h −1 ), 34 17Co/MnO x (213 mmol g −1 h −1 ), 35 10Co-7.1Ce/SEP (157 mmol g −1 h −1 ), 36 10Co/SEP (46 mmol g −1 h −1 ), 36 NiO/ZrO 2 (34 mmol g −1 h −1 ), 37 and Ni/ Al 2 O 3 (32 mmol g −1 h −1 ). 37 Except for the high ESR activity, the ESR hydrogen generation rate of Ni SA/CeO 2 fluctuated from 1650 to 1702 mmol g −1 h −1 , in a 24 h successive test at 500 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Martinelli et al [44] found that an interesting strategy to promote CO 2 formation instead of CO is the route of noble-metal-based catalyst doping via Na addition. Under selected operating conditions [45], which involved a quite diluted system and low space velocities (which means improved contact times between the catalyst and the reacting stream), at temperatures below 350 • C, the reaction mechanism did not involve carbon monoxide formation over a Cu/Al oxide catalyst.…”
Section: Strategymentioning
confidence: 99%